2001
DOI: 10.1111/1468-2419.00130
|View full text |Cite
|
Sign up to set email alerts
|

Problems in Knowledge Management: A Case Study of a Knowledge‐Intensive Company

Abstract: Knowledge management has become an important tool in staying ahead in the competition between companies. In this article five different phases of the knowledge management process are distinguished: acquiring knowledge, codifying knowledge, disseminating knowledge, developing knowledge and applying knowledge. The occurrence of knowledge management problems is demonstrated in a case study in a knowledge-intensive company. Most of the problems in this case occur in the first three phases of the knowledge manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 5 publications
0
12
0
2
Order By: Relevance
“…The 'priorities' inhibitor can be contrasted with the 'social ecology' at Nucor (Gupta & Govindarajan, 2000), where KM was truly seen as a priority for the organisation. The fear of failure at ICT (van Zolingen et al, 2001) can be identified with the 'weakness' inhibitor. The strong focus on individual procedures and regulations without reference to broader objectives characteristic of Russian culture (Michailova & Husted, 2003) can be identified with the 'individualism' inhibitor.…”
Section: Synthesis: a Model Of Cultural Inhibitorsmentioning
confidence: 99%
“…The 'priorities' inhibitor can be contrasted with the 'social ecology' at Nucor (Gupta & Govindarajan, 2000), where KM was truly seen as a priority for the organisation. The fear of failure at ICT (van Zolingen et al, 2001) can be identified with the 'weakness' inhibitor. The strong focus on individual procedures and regulations without reference to broader objectives characteristic of Russian culture (Michailova & Husted, 2003) can be identified with the 'individualism' inhibitor.…”
Section: Synthesis: a Model Of Cultural Inhibitorsmentioning
confidence: 99%
“…De acordo com Davenport e Prusak (1998), gestão do conhecimento é uma forma de identificar, gerir e valorizar o que a organização sabe. O maior número de estudos sobre Gestão do Conhecimento concebem a GC como processo (SPRENGER, 1995;SPEK E SPIJKERVET, 1995;GURTEEN, 1998;HARRIS, 1999;ZOLINGEM;STREUMER;STOOCKER, 2001;CHOO, 2006). Para a maioria desses autores a GC é formada pelos processos: aquisição, compartilhamento, institucionalização, Centro Universitário SOCIESC -UNISOCIESC Joinville, Santa Catarina, Brasil ISSN 2237-5163 / v. 07, n. 01: p. 33-49, ano 2017DOI: 10.14521/p2237-5163.2017 armazenamento e aplicação.…”
Section: Gestão Do Conhecimentounclassified
“…Similar to knowledge iden-ti¯cation (Van Zolingen et al, 2001), most organisations have a problem with these practices and do not have a systematic approach; the approaches used are few, ad hoc and reactive (Appelbaum et al, 2012;Daghfous et al, 2013). Rappaport et al (2003) propose di®erent strategies and practices for addressing the ageing workforce challenge.…”
Section: Transferring and Retaining Critical Knowledgementioning
confidence: 99%